Secondary metabolites, antioxidant activity, and acute toxicity of ethanol extract of Artocarpus elasticus leaves - Yafandi, Muchlis; Sabandar, Carla Wulandari; Dwidayati, Ari; Agusriyadin; Yulyana (Institut Teknologi Bandung, 2026)
Artocarpus elasticus belongs to Moraceae; a family best known for their fruits that support human life. Along with its nutritive components, different parts of A. elasticus are traditionally used to treat fever, hypertension, digestive problems, infections, and female fertility. However, scientific data of this plant, especially its leaves, are still limited, requiring further research. The present study investigated secondary metabolites, antioxidant, and acute toxicity of its leaves using methods on ethanolic maceration, phytochemical screening, determination of phenolics and flavonoids content, qualitative and quantitative DPPH radical scavenging activity, and brine shrimp lethality test. The yield of ethanolic extract of A. elasticus leaves was 6.52 gram extract per 100 gram of dried leaves. The study found the presence of alkaloids, flavonoids, tannins, terpenoids, steroids, and saponins in the extract. The TPC (28.29 ± 1.46 mg GAE/g of extract) and TFC (7.72 ± 0.34 mg QE/g of extract) found high in diluted extract at 10 and 100 µg/mL, respectively. The extract showed moderate free radical scavenging activity with an SC50 value of 8.04 µg/mL and an AAI of 0.99. The extract also displayed toxicity towards A. salina nauplii with an LC50 of 116.24 µg/mL. The study concludes that leaves of A. elasticus could be further explored for antioxidant and cytotoxic agents.